The Effect of Novel Fluorapatite Surfaces on Osteoblast-Like Cell Adhesion, Growth, and Mineralization - Liu, Jun (Mary Ann Liebert, Inc., 2010)
There is increasing demand for biomedical implants to correct skeletal defects caused by trauma, disease, or genetic disorder. In this study, the MG-63 cells were grown on metals coated with ordered and disordered fluorapatite (FA) crystal surfaces to study the biocompatibility, initial cellular response, and the underlying mechanisms during this process. The long-term growth and mineralization of the cells were also investigated. After 3 days, the cell numbers on etched metal surface are significantly higher than those on the ordered and disordered FA surfaces, but the initial adherence of a greater number of cells did not lead to earlier mineral formation at the cell–implant interface. Of the 84 cell adhesion and matrix-focused pathway genes, an up- or down-regulation of a total of 15 genes such as integrin molecules, integrin alpha M and integrin alpha 7 and 8 was noted, suggesting a modulating effect on these adhesion molecules by the ordered FA surface compared with the disordered. Osteocalcin expression and the mineral nodule formation are most evident on the FA surfaces after osteogenic induction (OI) for 7 weeks. The binding of the ordered FA surfaces to the metal, with and without OI, was significantly higher than that of the disordered FA surfaces with OI. Most significantly, even without the OI supplement, the MG-63 cells grown on FA crystal surfaces start to differentiate and mineralize, suggesting that the FA crystal could be a simple and bioactive implant coating material.